St. Mary's Augustinian Priory, Devenish Island, south window under tower, jamb - O'Donovan, Danielle (My University, 2008)
South window under tower, moudling comprses from intrados: quadrant, right-angled rebate, quadrant.
South window
Keywords: quadrant; Architecture, Gothic -- Ireland; Fermanagh (Northern Ireland); Architecture, Augustinian; Late Medieval; roll moldings